Surface Mechanism of Fe3+ Ions on the Improvement of Fine Monazite Flotation With Octyl Hydroxamate as the Collector - Zheng, Qingzhu; Qian, Yunlou; Zou, Dan; Wang, Zhen; Bai, Yang; Dai, Haidong (Frontiers in Chemistry, 2021)
Froth flotation of fine minerals has always been an important research direction in terms of theory and practice. In this paper, the effect and mechanism of Fe3+ on improving surface hydrophobicity and flotation of fine monazite using sodium octyl hydroxyamate (SOH) as a collector was investigated through a series of laboratory tests and detection measurements including micro flotation, fluorescence spectrum, zeta potential and X ray photoelectron spectrum (XPS).Flotation tests have shown that fine monazite particles (-26 + 15 μm) cannot be floated well with the SOH collector compared to the coarse fraction (-74 + 38 μm). However, adding a small amount of Fe3+ to the pulp before SOH can significantly improve the flotation of fine monazite. This is because the addition of Fe3+ promotes the adsorption of SOH and greatly improves the hydrophobicity of the monazite surface. This can result in the formation of a more uniform and dense hydrophobic adsorption layer, as shown by the fluorescence spectrum and zeta potential results. From the XPS results, Fe3+ reacts with surface O atoms on the surface of monazite to form a monazite-Osurf-Fe group that acts as a new additional active site for SOH adsorption. A schematic model was also proposed to explain the mechanism of Fe3+ for improving surface hydrophobicity and flotation of fine monazite using octyl hydroxamate as a collector. The innovative point of this study is using a simple reagent scheme to float fine mineral particles rather than traditional complex processes.